Use of 3d printing technology in the treatment of microtia and other outer ear deformities - Jakub Rezmer; Inga Wasilewska; Łukasz Świątek (Kazimierz Wielki University, 2022)
Introduction: Microtia and other outer ear deformations may cause a lot of psychical, social, and mental stress for a patient. In order to surgically treat it, we need a very experienced plastic surgeon specializing in such operations. With the use of 3D printing technology, such as fused deposition modeling or a sacrificial layer process there are a lot of possibilities starting from creating aids for plastic surgeons to printing ear prosthesis from live cells. Objective: The study's objective was to research, review and compare data available on PubMed about the use of 3D printing in the treatment of microtia and other ear deformations. A brief description of the state of knowledge: With the current state of knowledge, with the 3D printing technology, we can quickly create highly individualized and helpful training aids for plastic surgeons that would help them during operations. There is also a possibility of developing a personalized splint that would help correct the ears better than conventional methods. What's more, we can also print prosthetics, not only with the use of conventional materials used in 3D printing but also with live chondrocytes and adipocytes that were able to chondro and adipogenesis, respectively.  Conclusions: There are a couple of ways we can use 3D printing in the treatment of outer ear deformities. The most promising is printing with live cells, but we need more research to develop better methods and techniques to use in the future prosthetics.